Penerapan Pembelajaran Kooperatif Tipe Think Pair Share Untuk Meningkatkan Hasil Belajar IPS Terhadap Siswa Kelas VIII-1 SMP Negeri 2 Tanete Riaja Kabupaten Barru - Isabbang Isabbang (Universitas Negeri Makassar, 2021)
This type of research is a class action research (Classroom Action Research) which aims to improve social studies learning outcomes in Indonesian geographic and astronomical location material towards students of class VIII-1 SMP Negeri 2 Tanete Riaja. The subjects of this study were students of class VIII-1 Middle School 2 Tanete Riaja in Odd Semester 2019/2020 Academic Year as many as 27 students consisting of 17 men and 10 women. This research was conducted in two cycles. The research instruments used were observation sheets, response questionnaires, and learning achievement tests. Data were analyzed using descriptive statistics. The results obtained after taking action in the form of the application of Think-Pair-Share type of cooperative learning namely cycle I obtained an average score of 76.9 with a standard deviation of 11.00, then proceed to the second cycle, obtained an average score of 82.6 with a standard deviation of 4.95 in the medium category, also seen the progress of student activity in terms of activeness in the learning process. From the results of the analysis, it can be concluded that by applying cooperative learning Think-Pair-Share type can improve social learning outcomes of students of class VIII-2 of SMP Negeri 2 Tanete Riaja.